GAMBARAN KELEMBAGAAN MASYARAKAT DALAM PENGELOLAAN IRIGASI DI KABUPATEN BANTAENG - Burhanuddin Badrun; Andi Rumpang Yusuf (UNM Environmental Journals, 2022)
This study aims to find out the role of institutions in irrigation management. The type of research used is quantitative with a descriptive and correlational approach. The population in this study were all farmers in the irrigation area of Layoa Village, Bantaeng Regency. The sampling technique used purposive sampling in order to obtain 200 samples. Based on the results of the study it was found that the institutionalization of farmers in managing irrigation canals in Layoa Village, Bantaeng Regency was in the very high category. These results indicate that WUA's organizational ability in managing irrigation assets will result in a good understanding of farmers on how to distribute water. Furthermore, P3A organizations are also very concerned about the protection and implementation of irrigation systems that will reduce the risk of farmers' complaints about irrigation water regulations.